pH Regulation of Pectate Lyase Secretion Modulates the Attack of Colletotrichum gloeosporioides on Avocado Fruits - Yakoby, Nir (American Society for Microbiology, 2000)
Growth of Colletotrichum gloeosporioides in pectolytic enzyme-inducing medium (PEIM) increased the pH of the medium from 3.8 to 6.5. Pectate lyase (PL) secretion was detected when the pH reached 5.8, and the level of secretion increased up to pH 6.5. PL gene (pel) transcript production began at pH 5.0 and increased up to pH 5.7. PL secretion was never detected when the pH of the inducing medium was lower than 5.8 or when C. gloeosporioides hyphae were transferred from PL-secreting conditions at pH 6.5 to pH 3.8. This behavior differed from that of polygalacturonase (PG), where pg transcripts and protein secretion were detected at pH 5.0 and continued up to 5.7. Under in vivo conditions, the pH of unripe pericarp of freshly harvested avocado (Persea americana cv. Fuerte) fruits, resistant to C. gloeosporioides attack, was 5.2, whereas in ripe fruits, when decay symptoms were expressed, the pericarp pH had increased to 6.3. Two avocado cultivars, Ardit and Ettinger, which are resistant to C. gloeosporioides attack, had pericarp pHs of less than 5.5, which did not increase during ripening. The present results suggest that host pH regulates the secretion of PL and may affect C. gloeosporioides pathogenicity. The mechanism found in avocado may have equivalents in other postharvest pathosystems and suggests new approaches for breeding against and controlling postharvest diseases.